Comparison of Complete Nucleotide Sequence of rhaS Gene in the Strains of Plague Etiological Agent of Main and Minor Subspecies - L. M. Koukleva; G. A. Yeroshenko; V. E. Kouklev; Ya. M. Krasnov; N. P. Guseva; G. N. Odinokov; V. V. Kutyrev (Проблемы особо опасных инфекций, 2008)
Determined was complete nucleotide sequence of rhaS gene, the regulatory gene of rha locus of chromosome in Yersinia pestis strains of main and minor subspecies and in Y. pseudotuberculosis of I-III serovariants. The presence of significant and inessential nucleotide replacements in rhaS gene was shown. Evidently, these replacements are the cause of different abilities for rhamnose fermentation in the strains of plague etiological agent (main and minor subspecies) and those of pseudotuberculosis agent.